2009
DOI: 10.1073/pnas.0909773106
|View full text |Cite
|
Sign up to set email alerts
|

The helicase protein DHX29 promotes translation initiation, cell proliferation, and tumorigenesis

Abstract: Translational control plays an important role in cell growth and tumorigenesis. Cap-dependent translation initiation of mammalian mRNAs with structured 5 UTRs requires the DExH-box protein, DHX29, in vitro. Here we show that DHX29 is important for translation in vivo. Down-regulation of DHX29 leads to impaired translation, resulting in disassembly of polysomes and accumulation of mRNA-free 80S monomers. DHX29 depletion also impedes cancer cell growth in culture and in xenografts. Thus, DHX29 is a bona fide tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 37 publications
3
104
1
Order By: Relevance
“…72 These RNA helicases may assist eIF4A during the initiation step to enhance the process of ribosomal scanning on structured mRNAs, 97 as was recently described for the DEAH (Asp-Glu-Ala-His)-box protein DHX29. 98 The DEAD-box helicase DDX3 is not essential for global translation, but is required for the translation of specific transcripts (e.g., Cyclin E1) that contain secondary structures within their 5' UTRs. 99,100 We found that mTOR promotes the recruitment of DDX3 to the 5' mRNA cap in a 4E-BP1/2-dependent manner, 72 suggesting a mechanism whereby mTOR activity is required for the translation of DDX3-bound transcripts.…”
Section: Mtorc1 Regulates the Cap Recruitment Of A Network Of Translamentioning
confidence: 99%
“…72 These RNA helicases may assist eIF4A during the initiation step to enhance the process of ribosomal scanning on structured mRNAs, 97 as was recently described for the DEAH (Asp-Glu-Ala-His)-box protein DHX29. 98 The DEAD-box helicase DDX3 is not essential for global translation, but is required for the translation of specific transcripts (e.g., Cyclin E1) that contain secondary structures within their 5' UTRs. 99,100 We found that mTOR promotes the recruitment of DDX3 to the 5' mRNA cap in a 4E-BP1/2-dependent manner, 72 suggesting a mechanism whereby mTOR activity is required for the translation of DDX3-bound transcripts.…”
Section: Mtorc1 Regulates the Cap Recruitment Of A Network Of Translamentioning
confidence: 99%
“…Efficient translation initiation on mRNAs with structured 5 ′ -UTRs, which are more prevalent in higher eukaryotes, requires the specific DExH-box helicase DHX29 in vitro and in vivo (Pisareva et al 2008;Parsyan et al 2009). DHX29 depletion is also shown to impede cancer cell growth in culture and in xenografts, which suggests a role for this protein in tumorigenesis (Parsyan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…DHX29 depletion is also shown to impede cancer cell growth in culture and in xenografts, which suggests a role for this protein in tumorigenesis (Parsyan et al 2009). Until the recent discovery of mammalian-specific DHX29, eIF4A was the only reported helicase with a confirmed role in canonical eukaryotic translation initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Many characterized RNA helicases have been found to be fundamental in essential cellular processes (1,26). In recent years, a few RNA helicases have been found to participate in cancer development even though their detailed molecular mechanisms remain largely undiscovered (27)(28)(29)(30)(31)(32)(33). Furthermore, despite the characterization of several DEAD/DEAH proteins, few specific inhibitors targeting these ATP-dependent helicases have been developed.…”
Section: Discussionmentioning
confidence: 99%